Gender Mapping in Vegetable Cultivation in Sangrur and Patiala districts of Punjab - Mittal, Ritu; Kaur, Gurmehar (Indian Journal of Extension Education, 2021)
The present study was undertaken to investigate gender participation in vegetable cultivation in Sangrur and Patiala districts of Punjab. Male and female labourers as well as cultivators were selected randomly as respondents. The results of the study show that participation of men was significantly more in procurement of inputs, nursery management and land preparation. Among various intercultural operations, hoeing and weeding was performed more by female while irrigation, earthing and thinning by male. In all plant protectionmeasures and fertilizer application, participation of male was high while harvesting was majorly female’s job. In marketing of vegetables, participation of males was much higher than females whose participation was reported negligible. The study recommends that extension trainings should select trainees depending upon the gender mapping in vegetable cultivation so that both men and women could perform their roles in agriculture efficiently and thus increase their family income.